Determinants of Tax Avoidance Among Lq45-Listed Firms: Examining the Moderating Effect of Profitability on Ownership Structure and Related Party Transactions - Dea Dani Lestari; Diana Sari (Journal Research of Social Science, Economics, and Management, 2026)
Tax revenue in Indonesia is still considered to have not reached an optimal level. Indonesia ranks fourth in the Asian region in terms of tax avoidance practices, indicating a relatively high level of avoidance. Tax revenue remains suboptimal due to tax avoidance behaviors arising from business activities that exploit loopholes in applicable tax regulations. This research aims to examine the effect of foreign ownership and related party transactions on tax avoidance and profitability, with moderating variables. The study employs a descriptive method with a quantitative approach. The sampling technique used is purposive sampling, involving 26 companies. The analytical method applied is moderated regression analysis, conducted using SPSS version 25. The results of the study show that foreign ownership has a significant effect on tax avoidance, while related party transactions do not have a significant effect. Furthermore, profitability is able to moderate the relationship between foreign ownership and related party transactions on tax avoidance. Overall, foreign ownership and profitability influence tax avoidance, whereas  related party transactions do not show a significant effect.